In support of open-loop supply chains: Expanding the scope of environmental sustainability in reverse supply chains - M Kalverkamp; SB Young (Journal of Cleaner Production, 2019)
This study expands the environmental sustainability paradigm of reverse supply chains. The study examines the notion of closed-loop supply chains and suggests the use of the term in academia and business is too limited from a sustainability perspective. Three case examples in automotive remanufacturing were chosen to represent a global, multi-tier industry with documented circular economy strategies. A simple conceptual framework is developed that bridges different concepts of “loops” at whole product, component and material levels, and which is then used to show that closed-loop supply chains that focus on OEM activities appear to overlook alternative models of reverse supply chain loops. The study considers how these alternative loops contribute to environmental sustainability by looking at market dynamics and relations between business actors in supply chains in automotive remanufacturing. Alternative loops may contribute to product displacement activities in the market and thus provide positive environmental and resource results. The narrow focus on “closed loops” in supply-chain research and industry simplifies potential benefits and weaknesses, and overlooks the contribution of “open loops” in supply chains, which enable business innovation and can improve sustainability outcomes in product and material supply chains. This article fills a void in supply chain management research and argues for a more adaptive management approach to reverse supply chains for end-of-life products.